Idiopathic Granulomatous Mastitis Presenting as a Breast Pseudotumor: Case Reports with Review of the Literature - Nour Abdul Halim; Imad Uthman; Rayan Rammal; Hazem I. Assi (Case Reports in Rheumatology)
Idiopathic granulomatous mastitis is a rare benign inflammatory breast disease that affects women of childbearing age with a history of breastfeeding. It usually presents as an enlarging breast mass that can greatly mimic breast cancer. Moreover, it does not have a specific radiographic finding, so the only way to reach a definitive diagnosis is by core biopsy and histology. Furthermore, a consensus regarding the best treatment modality has not been reached yet. In this report, we describe the cases of two patients who suffered from this disease, and to our knowledge, such a report is the first of its kind to address this topic in this region. Therefore, because of its uncommon nature and obscure presentation, we hereby report two cases of idiopathic granulomatous mastitis. The clinical presentation, treatment, and pathological findings are described, and a literature review on idiopathic granulomatous mastitis will be reported.